2016
DOI: 10.5005/jp-journals-10024-1812
|View full text |Cite
|
Sign up to set email alerts
|

Action of Chlorhexidine, Zingiber officinale, and Calcium Hydroxide on Candida albicans, Enterococcus faecalis, Escherichia coli, and Endotoxin in the Root Canals

Abstract: Aim:The purpose of this in vitro study was to evaluate the antimicrobial activity of 2% chlorhexidine gel (CHX) as auxiliary chemical substance and intracanal medications on Candida albicans, Enterococcus faecalis, Escherichia coli, and their endotoxins in the root canals. Materials and methods:The study was conducted on 48 single-rooted human teeth divided into four groups (n = 12), according to intracanal medications used: (1) Calcium hydroxide + apyrogenic saline solution (Ca(OH) 2 + SS), (2) 20% ginger gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Diverse plant extracts were used in dentistry principally as endodontic irrigant or intracanal medication (Horiba, Maekawa, Ito, Matsumoto, & Nakamura, 1991;Maekawa et al, 2015;Qunqiang & Farnham, 1989;Marcia C Valera et al, 2016) or even associated with other intracanal medication (Marcia Carneiro Valera et al, 2015) and this may be related to the fact of the increased resistance of micro-organisms against antibiotics overtime (Jungermann et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diverse plant extracts were used in dentistry principally as endodontic irrigant or intracanal medication (Horiba, Maekawa, Ito, Matsumoto, & Nakamura, 1991;Maekawa et al, 2015;Qunqiang & Farnham, 1989;Marcia C Valera et al, 2016) or even associated with other intracanal medication (Marcia Carneiro Valera et al, 2015) and this may be related to the fact of the increased resistance of micro-organisms against antibiotics overtime (Jungermann et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Phytotherapy was used in dentistry and more specifically in endodontics since the last century (Groppo et al, 2008) due to its antimicrobial, anti-inflammatory and antifungal actions and because it is considered biocompatible (Guandalini Cunha et al, 2020;De La Chapa, Singha, Lee, & Gonzales, 2018;Marcia C Valera et al, 2016;Viegas et al, 2020) in addition to other techniques like photodynamic therapy and passive ultrasonic irrigation (Abu Hasna, Ferrari, & Talge Carvalho, 2019;Abu Hasna, Khoury, et al, 2020;Abu Hasna, Pereira Da Silva, et al, 2020). This use was encouraged by the World Health Organization (WHO); however, the agency establishes specific safety requirements including traditional use certificate and toxicity analyzes of the extracts (Organization, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Valera et al (2016), it was suggested that Z. officinale Roscoe may be clinically applicable as a root canal irrigant as 20% Z. officinale glycolic extracts were effective in reducing the endotoxins and microorganisms implicated in endodontic infections such as Candida albicans and Enterococcus faecalis.…”
Section: Zingiber Officinale Roscoe (Ginger)mentioning
confidence: 99%
“…can be associated with chronic periodontal diseases and endodontic infections [6,7].The presence of enterococci within the root canal has been associated with persistent endodontic and periapical infections, being E. faecalis the most prevalent specie [8][9][10][11]. E. faecalis play an important role in post-treatment diseases because this specie can show high resistance to conventional antimicrobial agents, such as sodium hypochlorite, chlorhexidine, and calcium hydroxide [12][13][14]. In addition, certain clinical isolates of E. faecalis recovered from root canal infections demonstrated resistant to several antibiotics recommended for dental procedures, such as benzylpenicillin, ampicillin, clindamycin, and tetracycline [15], cephalosporins [8], azithromycin, and erythromycin [12].…”
Section: Introductionmentioning
confidence: 99%